Assessing the causal effects of long-term exposure to PM2.5 during pregnancy on cognitive function in the adolescence: Evidence from a nationwide cohort in China. (15th January 2022) - Xu, Zongyou; Liu, Zhenmi; Lu, Liyong; Liao, Weibin; Yang, Chenyu; Duan, Zhongxin; Zhou, Qian; He, Wenchong; Zhang, En; Li, Ningxiu; Ju, Ke
Abstract: The effects of air pollution on adolescents need further consideration. Although there is evidence that maternal exposure to air pollution may affect the cognitive function of offspring, relevant studies remain limited and inconsistent, with a lack of studies assessing the causal effects and evidence from developing countries. Using data from Chinese Family Panel Studies, a representative Chinese nationwide cohort study, OLS combined with instrumental variable + two-stage least square (IV+2SLS) was used to explore the causal effects of exposure to PM2.5 concentrations during pregnancy on the cognitive function of offspring when they become adolescents. After detailed argumentation and multiple testing, Planetary Boundary Layer Height (PBLH) and Surface Pressure (SP) were selected as the instrumental variables for this study. One thousand five hundred fifty-five adolescents participated in this study, with a mean age of 13.3 years ( sd = 2.3). There were 706 females (45.4%), the mean maternal PM2.5 exposure concentration was 64.9 μ g / m 3, and recorded a mean cognitive function score of 38.1 ( sd = 9.4). The OLS results found that maternal exposure to air pollution increased cognitive function in offspring adolescents, corroborating the presence of endogeneity. Multi-domain knowledge, the results of the weak instrumental variable assessments of F -tests ( F = 237 > 10) and Stock-yogo tests ( minimum eigenvalue statistic = 153.16 > 16.38), and the results of the Hansen J overidentification test ( p > 0.05) verified the plausibility and validity of the instrumental variables. The IV+2SLS results, following causal modeling, showed that PM2.5 exposure during pregnancy impairs the cognitive ability of offspring adolescents ( β = −0.040, p < 0.05). Robustness tests also validated the results. This study provides important policy implications for developing countries on protecting their adolescents and reminds parents that the protection of adolescents from air pollution should begin from conception. Graphical abstract: Image 1 Highlights: Adverse effects of air pollution on the cognitive abilities of adolescents. Evidence from a representative Chinese national cohort study. The ideal instrumental variables were selected after detailed arguments and tests. The endogeneity was verified, and the causal model was used to obtain true effects. Protecting adolescence from air pollution should start during pregnancy.